2010
DOI: 10.1111/j.1744-7917.2010.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies on malathion resistance, inheritance and association of carboxylesterase activity in brown planthopper, Nilaparvata lugens complex in Peninsular Malaysia

Abstract: Two sympatric populations of brown planthopper (BPH), one from rice and the other from Leersia hexandra were collected from each of five locations in Malaysia. All the tested malathion‐resistant individuals of the rice BPH population and F1 generation (cross between malathion‐resistant [usually caught on rice] and malathion‐susceptible [usually caught on Leersia]) showed high esterase activity, while all malathion‐susceptible individuals on L. hexandra showed low esterase activity. In the F2 generation, all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(52 reference statements)
1
3
0
1
Order By: Relevance
“…AMOVA was performed and was confirmed the differentiation into two groups of Aphid gossypii [ 32 ], five groups of Acorus gramineus [ 33 ], and two groups of natural populations of the wild rice, Oryza rufipogon [ 34 ]. Therefore, our molecular data of DALP-PCR indicated that brown plant hopper (BPH) with high esterase activity usually captured from rice plant and those with low esterase activity, usually captured from L. hexandra in Malaysia, represent two distinct closely related species and supported previous results as reported by Latif et al [ 6 , 7 , 35 ]. Although DALP molecular method is not new, but so far to our knowledge this study is the first to detect genetic polymorphism in rice brown planthopper complex using this method.…”
Section: Discussionsupporting
confidence: 90%
“…AMOVA was performed and was confirmed the differentiation into two groups of Aphid gossypii [ 32 ], five groups of Acorus gramineus [ 33 ], and two groups of natural populations of the wild rice, Oryza rufipogon [ 34 ]. Therefore, our molecular data of DALP-PCR indicated that brown plant hopper (BPH) with high esterase activity usually captured from rice plant and those with low esterase activity, usually captured from L. hexandra in Malaysia, represent two distinct closely related species and supported previous results as reported by Latif et al [ 6 , 7 , 35 ]. Although DALP molecular method is not new, but so far to our knowledge this study is the first to detect genetic polymorphism in rice brown planthopper complex using this method.…”
Section: Discussionsupporting
confidence: 90%
“…However, it was surprising that DEF and TPP, which are known to neutralize ESTs, failed to signiÞcantly reduce the resistance level of permethrin and etofenprox. High ESTs activities are also associated with organophosphate resistance (Latif et al 2010), and this could explain the onset of temephos resistance in all populations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major destructive dominant herbivore of rice is N. lugens that is found in all rice-growing areas of Indonesia, Thailand, India, Japan, Vietnam, China, Bangladesh, Solomon Island and north-eastern Australia, the Philippines, and Malaysia (Masaya et al, 2008;Latif et al, 2010;Ali et al, 2014;Hereward et al, 2020). The long distance migratory behavior and population development patterns sometimes make the control measure more complex and most of the rice field of different places became Insecticide Resistance in the Brown Planthopper, Nilaparvata lugens vulnerable to the pest (Khoa, Thang, Liem, Holst, & Kristensen, 2018).…”
Section: Nilaparvata Lugens a Destructive Pest Of Ricementioning
confidence: 99%
“…Numerous resistance mechanisms have been found governing insect resistance to insecticides (Garrood et al, 2016). Among the two mostly reported resistance mechanisms, the enhanced metabolic detoxification of xenobiotics has been commonly studied in N. lugens (Latif, Omar, Tan, Siraj, & Ismail, 2010). Increased activities of detoxifying enzymes have been constantly found in resistant N. lugens.…”
Section: Introductionmentioning
confidence: 99%